Green catalyst Fe(OTs)(3)/SiO2 for the synthesis of 4-Pyrrolo-12-oxoquinazolines - Allaka, Bhargava Sai; Basavoju, Srinivas; Krishna, Gamidi Rama (ChemistrySelect, 2020)
An efficient and eco-friendly diversity-oriented synthetic protocol has been presented to synthesize structurally versatile drug-like molecules under solvent-free grinding in the presence of Fe(OTs)(3)/SiO2 as a catalyst. The use of Fe(OTs)(3)/SiO2 as a recyclable and reusable catalyst has been explored in the synthetic domino protocol involving one-pot, three component reaction for the synthesis of 4-pyrrolo-12-oxoquinazolines with special features of the protocol like high atom-economy, operational simplicity, short reaction time and high selectivity with excellent yields.
Keywords: 4-Pyrrolo-12-oxoquinazolines; Fe(OTs)(3); Green methodology; Liquid Assisted Grinding (LAG); SiO2 catalyst; Solvent-free grinding

Photoinduced multicomponent regioselective synthesis of 1,4,5-trisubstituted-1,2,3-triazoles: transition metal-, azide- and oxidant-free protocol - Sai Allaka, Bhargava; Basavoju, Srinivas; Rama Krishna, Gamidi (Advanced Synthesis & Catalysis, 2021)
A transition metal- and azide-free approach is explored to synthesize 1,4,5-trisubstituted-1,2,3-triazoles under sunlight. The reaction proceeds via C-N and N-N bond formations. These regioselective 1,2,3-triazoles are obtained from isatin Schiff bases, benzaldehydes and tosylhydrazine in the presence of base. This protocol offers the structurally diverse 1,2,3-triazole derivatives with 75-90% yields.
Keywords: 1; 2; 3-triazoles; 4; 5-trisubstituted-1; azide- and oxidant free protocol; Cycloaddition; milder reaction conditions; molecular diversity; Multicomponent reaction; Regioselectivity; transition metal-

Transition metal- and oxidant-free regioselective synthesis of 3,4,5-trisubstituted pyrazoles by means of [3+2] cycloaddition reactions - Allaka, Bhargava Sai; Basavoju, Srinivas; Gamidi, Rama Krishna (ChemistrySelect, 2022)
A highly efficient regioselective synthesis of 3,4,5-trisubstituted pyrazoles via transition metal- and oxidant-free, three component [3+2] cycloaddition with thiazolidinedione chalcones, benzaldehydes and N-tosylhydrazine is described. The reaction proceeds through C-C and C-N bond formations under mild reaction conditions to produce structurally diverse polysubstituted pyrazoles in moderate to good yields.
Keywords: 3; 4; 5-trisubstituted pyrazoles; Cycloaddition; Multicomponent reaction; Oxidant free; Regioselectivity; Transition metal free

Design and synthesis of novel quinazolinyl-bisspirooxindoles as potent anti-tubercular agents: an ultrasound-promoted methodology - Allaka, Bhargava Sai; Basavoju, Srinivas; Rekha, Estharla Madhu; Sriram, Dharmarajan; Krishna, Gamidi Rama (Molecular Diversity, 2023)
The essential need for the potent anti-tubercular (anti-TB) agents with high selectivity and safety profile prompted us to synthesize a new series of quinazolinyl-bisspirooxindoles. The title compounds were synthesized by one-pot multicomponent [3 +2] cycloaddition reaction under ultrasonication. Further, in vitro anti-TB activity was evaluated against Mycobacterium tuberculosis H37Rv. Among the screened compounds, two compounds (4q and 4x) showed potent activity with MIC value 1.56 mu g/mL and four compounds exhibited significant activity (MIC =3.125 mu g/mL), and also cytotoxicity studies against RAW 264.7 cell lines reveal that most active compounds were less toxic to humans. In addition, in order to demonstrate the inhibitory properties, molecular docking studies were carried out and the results showed that the target compounds have good binding energy and better binding affinity within the active pocket, thus these compounds may consider to be as potent inhibitors toward selective targets.
Keywords: anti-tubercular activity; bisspirooxindoles; Cytotoxicity screening; Molecular docking studies; ultrasonication

Ultrasound assisted green protocol for the synthesis of quinoxaline based bisspirooxindoles: crystal structure analysis, enone umpolung, DFT calculations, anti-cancer activity, and molecular docking studies - Baddepuri, Sravanthi; Allaka, Bhargava Sai; Gamidi, Rama Krishna; Faizan, Mohmmad; Pawar, Ravinder; Basavoju, Srinivas (Synthetic Communications, 2023)
A series of novel quinoxaline based bisspirooxindolo-pyrrolizidines were synthesized through 1,3-dipolar cycloaddition under ultrasonication with shorter reaction time and good yields. The compounds were well characterized by various spectroscopic methods and finally single crystal X-ray diffraction method (4c, 4d). DFT energy calculations confirm the regioselectivity due to enone umpolung effect. The in vitro anti-cancer activity of the synthesized compounds (4a-s) shows that the compounds 4g and 4q exhibited good anti-cancer activity with IC50 values14.51 +/- 1.1 and 11.36 +/- 0.23 mu M against DU-145 prostate cancer cell line; and 16.78 +/- 0.95 and 14.28 +/- 0.64 mu M against Hela cervical cancer cell lines when compared to the standard anti-cancer drug doxorubicin (1.75 +/- 0.06 and 1.35 +/- 0.09 mu M). In silico molecular docking studies indicated that the synthesized compounds may serve as a potential lead for the further development of novel anti-cancer agents.
Keywords: Anti-cancer activity; bisspirooxindoles; DFT calculations; Hirshfeld surface; ultrasonication

Ultrasound assisted synthesis of spirooxindolo-1,2,4-oxadiazoles via [3+2] cycloaddition reaction and their anti-cancer activity - Kanchrana, Madhu; Allaka, Bhargava Sai; Krishna, Gamidi Rama; Basavoju, Srinivas (ARKIVOC, 2023)

Design, synthesis, anti-mycobacterial activity, molecular docking and ADME analysis of spiroquinoxaline-1,2,4-oxadiazoles via [3+2] cycloaddition reaction under ultrasound irradiation - Kanchrana, Madhu; Gamidi, Rama Krishna; Kumari, Jyothi; Sriram, Dharmarajan; Basavoju, Srinivas (MOLECULAR DIVERSITY, 2024)
Keywords: 2; 4-oxadiazoles; cytotoxicity activity; molecular; Mycobacterium tuberculosis; Spiroquinoxaline-1

Ionic liquid assisted green synthesis of quinoxaline based bisspirooxindoles: anticancer evaluation and molecular dynamics - Kanchrana, Madhu; Krishna, Gamidi Rama; Dey, Biswajit; Pandey, Nandita; Guru, Santosh Kumar; Sangolkar, Akanksha Ashok; Pawar, Ravinder; Basavoju, Srinivas (CHEMISTRYSELECT, 2024)
Keywords: Cycloaddition; spirooxindoles

Synthesis of quinazolinone based spirocyclopropanes via [3?+?2] cycloaddition reaction: in silico anti-tubercular molecular docking studies and ADME prediction - Allaka, Bhargava Sai; Kanchrana, Madhu; Gamidi, Rama Krishna; Basavoju, Srinivas (Polycyclic Aromatic Compounds, 2024)
A highly efficient cascade annulation approach is developed for the synthesis of novel quinazolinone-based spirocyclopropanes via three-component [3 + 2] cycloaddition reaction with aldehydes, tosylhydrazide and quinazolinyl chalcones. The reaction features the formation of two C–C bonds and three stereogenic centers. A variety of highly functionalized spirocyclopropyl quinazolinones were obtained in good yields under mild reaction conditions. Furthermore, in silico anti-tubercular (anti-TB) molecular docking studies were performed for the generated compounds against three Mycobacterium tuberculosis proteins with PDBID: 1DF7, 1P44 and 4TZK. ADME prediction were evaluated for the drug like properties of the synthesized compounds.

Ultrasound-assisted ionic liquid-mediated green method for synthesis of 1,3-diphenylpyrazole-based spirooxindolopyrrolizidines, their anti-tubercular activity, molecular docking study and ADME predictions - Baddepuri, Sravanthi; Gamidi, Rama Krishna; Kumari, Jyothi; Sriram, Dharmarajan; Basavoju, Srinivas (New Journal of Chemistry, 2024)
The aim of the study is to develop the synthesis of a novel series of potent anti-tubercular (anti-TB) activity of 1,3-diphenylpyrazole-based spirooxindolopyrrolizidine derivatives via an efficient green approach achieved by using an ionic liquid ([Bmim]BF4) under ultrasonication. The title compounds 4a-4ad with a general molecular formula CaHbX(0-2)NcOd (X = F/Cl/Br) were produced with high yields in shorter reaction time and well characterized by using spectral techniques; and finally single crystal X-ray diffraction method (4b). The newly synthesized compounds were evaluated for their in vitro anti-TB activity against Mycobacterium tuberculosis H37Rv strain. Among all, six compounds 4e (C36H29N5O4), 4g (C34H28N4O3), 4q (C36H28F2N4O2), 4r (C36H28ClFN4O2), 4y (C36H29BrN4O2) and 4z (C36H28BrFN4O2) exhibited significant anti-TB activity with MIC value 6.25 mu g mL-1, when compared to the standard drug ethambutol (MIC:1.56 mu g mL-1). In silico molecular docking studies were performed against M. tuberculosis enoyl-acyl carrier protein reductase inhibitor. The compounds 4o, 4p, 4y and 4aa were exhibited least binding energies -12.58, -12.61, -12.58 and -12.57 kcal mol-1, respectively. These results reveal that the produced compounds might be used for the future generation of novel anti-TB drugs. The study aims to develop and synthesis of a novel series of 1,3-diphenylpyrazole-based spirooxindolopyrrolizidine derivatives as potent anti-TB agents via an efficient green approach by using an ionic liquid ([Bmim]BF4) under ultrasonication.

Green one-pot three component synthesis of thiazolidine-2,4-dione based bisspirooxindolo-pyrrolidines with [Bmim]BF4: their in vitro and in silico anti-TB studies - Rukyanaik, V.; Gamidi, Rama Krishna; Kumari, Jyothi; Sriram, Dharmarajan; Basavoju, Srinivas (Molecular Diversity, 2025)
A simple and effective three-component one-pot green methodology was employed for the synthesis of a new thiazolidine-2,4-dione based bisspirooxindolo-pyrrolidine derivatives using [Bmim]BF4 ionic liquid via [3 + 2] cycloaddition reaction. It is an environmentally benign, column chromatography-free, shorter reaction time, good yield and easy product isolation method. The synthesized compounds 10a-x, were thoroughly characterized by using various spectroscopic methods like FT-IR, H-1 NMR, C-13 NMR, Mass spectrometry and finally by single crystal X-ray diffraction method. In vitro anti-tubercular (anti-TB) activity studies were carried out on these synthesized compounds, and they showed good to moderate anti-TB activity against Mycobacterium tuberculosis H37Rv strain. The compound 10a exhibited good anti-TB activity, with an MIC (Minimum Inhibitory Concentration) value of 12.5 mu g/mL, and the compounds 10m, 10o and 10r showed moderate activity with an MIC value of 25.0 mu g/mL. Remaining compounds exhibited poor activity against Mycobacterium tuberculosis. Ethambutol, rifampicin and isoniazid were used as standard drugs. Furthermore, in silico molecular docking experiments on the TB protein (PDB ID: 1DF7) were carried out to understand the binding interactions, and they showed least binding energy values ranging from -8.9 to -7.2 kcal/mol.
Keywords: 4-dione based bisspirooxindolo-pyrrolidines; Anti-TB activity; green synthesis; Molecular docking; Thiazolidine-2; [3+2] cycloaddition reaction; [Bmim]BF4

An ultrasound-assisted green synthesis of 1,3-diphenyl pyrazole-based spirooxindolo-1,2,4-oxadiazoles: their in vitro anti-tubercular activity and in silico molecular dynamics - Baddepuri, Sravanthi; Gamidi, Rama Krishna; Kumari, Jyothi; Sriram, Dharmarajan; Gangarapu, Kiran; Basavoju, Srinivas (Chemistryselect, 2025)
A simple base-mediated one-pot synthetic green methodology has been successfully employed for the synthesis of 1,3-diphenylpyrazole-based spirooxindolo-1,2,4-oxadiazole derivatives. The newly synthesized analogues were tested for their in vitro anti-tubercular activity (anti-TB) against Mycobacterium tuberculosis H37Rv strain, and the results were reported as minimum inhibitory concentration (MIC) values ranging from 3.125 to 25 mu g/mL. Especially, the five compounds 3a, 3f, 3k, 3q, and 3v exhibited good to moderate anti-TB activity with MIC of 3.125 mu g/mL when compared to the reference drug ethambutol (MIC: 1.56 mu g/mL). In silico Molecular docking and molecular dynamics simulations of the protein-ligand complex (3a, 3f, 3k, and 3v) against Mycobacterium tuberculosis DprE1 (PDB ID: 5OEQ) of M. tuberculosis H37Rv strain revealed that these four compounds could be promising anti-mycobacterial candidates, as evident from the binding results and stability of the docked-ligand complexes with considerable least binding energies. ADME parameters were also studied to assess the drug likeness, which clearly shows that the newly developed compounds might be useful for the future development of novel anti-tubercular drugs.
Keywords: 1; 2; 4-oxadiazoles; In silico molecular dynamic studies; In vitro anti-tubercular activity; ultrasonication